PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI - Funawati, Restu; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of profitability to firm value with CSR as moderating variable. variable. The population in this research is 43 mining companies which are listed Indonesia Stock Exchange (IDX) in 2014-2016 periods. The sample collecction technique has been carried out by using purposive sampling method and it has generated 48 samples during 2014-2016 periods. The data is the secondary data which has been obtained by using documentation technique consists of the 2014-2016 annual report of the mining companies.  The data analysis method in this research is the multiple linear regressions and 23rd version SPSS for windows. The result of the research shows that profitability give influence to the firm value, the CSR gives positives influence to the firm value, the CSR disclosure does not moderate the correlation between profitability and firm value.Keywords: Profitability, firm value, Corporate Social Responsibility disclosure